2010
DOI: 10.1590/s1807-55092010000400002
|View full text |Cite
|
Sign up to set email alerts
|

O nível de aptidão física afeta o desempenho do árbitro de futebol?

Abstract: Os objetivos do presente estudo foram: a) descrever a demanda física imposta aos árbitros de futebol brasileiros durante partidas oficiais e b) analisar se o nível de aptidão física interfere no desempenho da arbitragem. Os árbitros (n = 11) foram avaliados durante jogos oficiais (n = 21) do campeonato Potiguar 2009. A média de idade foi de 36,36 ± 6,34 anos. A distância percorrida, a velocidade (média e máxima) e a frequência cardíaca (média e máxima) foram registradas durante as partidas. A análise da arbitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Finally, soccer referees generally have a good athletic condition characterized by excellent levels of cardiorespiratory fitness, such as resting bradycardia. [2][3][4]12,26 In agreement with previous studies, resting ECG demonstrated this characteristic in the referees of the present study. 27,28 In the evaluation during effort, the sample showed satisfactory values of reserve HR and increase of resting HR to HR at the point of maximum effort, considered an important predictor of cardiovascular diseases and sudden death.…”
Section: Good Excellentsupporting
confidence: 92%
See 4 more Smart Citations
“…Finally, soccer referees generally have a good athletic condition characterized by excellent levels of cardiorespiratory fitness, such as resting bradycardia. [2][3][4]12,26 In agreement with previous studies, resting ECG demonstrated this characteristic in the referees of the present study. 27,28 In the evaluation during effort, the sample showed satisfactory values of reserve HR and increase of resting HR to HR at the point of maximum effort, considered an important predictor of cardiovascular diseases and sudden death.…”
Section: Good Excellentsupporting
confidence: 92%
“…In the literature, it is well established that the physical condition of the referees has a large influence on their technical performance during matches. 3 In addition, few studies have addressed the health of these professionals, who are less attended by the regulators of the sport. 2,12,15,16 The main findings of the present study emphasize that, even when working in leagues of lower tiers or levels and with fewer working conditions, the FES capixabas referees present a low risk for the development of chronic diseases, as well as a good body structure and physical fitness to work in regional, national, or international matches.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations